Clinical Observation of Levothyroxine Sodium Combined with Selenium in the Treatment of Patients with Chronic Lymphocytic Thyroiditis and Hypothyroidism and the Effects on Thyroid Function, Mood, and Inflammatory Factors - Chunping Sun (Hindawi Limited, 2021)
The purpose of this study was to investigate the therapeutic effects of levothyroxine sodium combined with selenium treatment and single levothyroxine sodium treatment on patients with chronic lymphocytic thyroiditis and hypothyroidism and to analyze the effects of different treatment regimens on patients’ thyroid function, mood, and inflammatory factors, with the aim of providing a reference for clinical treatment. The subjects of the current study were 138 chronic lymphocytic thyroiditis (CLT) patients with hypothyroidism admitted to our hospital from May 2016 to September 2019 and were randomly divided into a control group taking levothyroxine sodium (LT4) treatment and a combined group of LT4 combined with selenium treatment, with 69 cases each. Patients in both groups were evaluated for efficacy after 3 months of treatment, and their thyroid function was observed by total triiodothyronine (TT3), total thyroxine (TT4), thyroid stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb), and thyroid globulin antibody (TGAb), and their mood changes were observed by Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores. The levels of inflammatory factors such as interleukin-2 (IL-2), interleukin-10 (IL-10), and tumor necrosis factor-α (TNF-α) were measured, and the occurrence of adverse drug reactions during the treatment period was observed and recorded in all patients. The results showed that the total effective rate of the combined group was significantly higher than that of the control group. The levels of TT3, TT4, TSH, TgAb, and TPOAb, SAS and SDS scores, and levels of inflammatory factors such as IL-2, IL-10, and TNF-α were significantly improved in both groups after treatment. Compared with the control group, TGAb, TPOAb, IL-2, TNF-α levels, and SAS and SDS scores decreased more and IL-10 levels increased more in the combined group, while the differences of other indexes were not statistically significant. This suggests that LT4 has certain efficacy in treating CLT with hypothyroidism, and the combined selenium treatment can improve the therapeutic effect of LT4 and can play a greater role in improving patients’ mood and immune and inflammatory responses.